Ultrasound-guided non-invasive retraction for strangulated obturator hernia allows elective radical surgery: analysis of 12 cases - Yuto Maeda; Osamu Nakahara; Seiya Saito; Jiro Nasu; Hideo Baba (Surgical Case Reports, 2021)
Abstract Background Obturator hernia is a life-threatening condition, requiring emergency intervention due to strangulation, if non-invasive repair for strangulation cannot be complete. Change from emergency surgery to elective surgery using minimal non-invasive options can greatly contribute to perioperative safety and curability of the underlying disease. Case presentation 12 cases of strangulated obturator hernia from April 2013 to February 2020 with male:female patient ratio of 0:12. Reduction under ultrasound guidance was possible amongst 10 out of 12 cases. The average age was 85.3 years (74–97) and average BMI was 17.4 (15.0–20.1). Based on physical findings and CT examination, diagnosis of obturator hernia was made using echo guided non-invasive reduction. Prevention in the intestinal ischemia and perforation was observed in the treated cases. Upon request, elective radical surgery was performed in 7 of these patients after their condition improved and monitored other organs for any signs. Conclusion Attempt to improve the strangulation of obturator hernia under an echo-guided approach could enable elective and safe surgery and is believed to be a diagnostic treatment worth attempting.